2012
DOI: 10.1159/000341411
|View full text |Cite
|
Sign up to set email alerts
|

Does Alzheimer’s Disease Protect against Cancers? A Nationwide Population-Based Study

Abstract: Background: Previous studies suggested a decreased risk of cancer among patients with Alzheimer’s disease (AD). There is still a lack of data on the specific types of cancer, the risk factors, and the impact of cholinesterase inhibitors on developing cancer in AD. Methods: We performed a nationwide population-based study of 6,960 patients with AD between 1997 and 2006 using Taiwan’s National Health Insurance database. Patterns of cancer incidence in AD patients were compared with those of the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 76 publications
5
82
3
2
Order By: Relevance
“…In 2010, Attner et al [10 ]performed a population-based study of 18 cancer types in a Swedish population and found that patients with dementia have a lower risk of cancer. Similarly, in a recent population-based study of 6,960 patients with Alzheimer dementia in Taiwan, those patients were found to have a reduced overall risk of developing cancer [11]. Later, in 2015, Shi et al [12] conducted a meta-analysis of data from 9 publications and concluded that the risk of cancer is significantly decreased in Alzheimer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Attner et al [10 ]performed a population-based study of 18 cancer types in a Swedish population and found that patients with dementia have a lower risk of cancer. Similarly, in a recent population-based study of 6,960 patients with Alzheimer dementia in Taiwan, those patients were found to have a reduced overall risk of developing cancer [11]. Later, in 2015, Shi et al [12] conducted a meta-analysis of data from 9 publications and concluded that the risk of cancer is significantly decreased in Alzheimer patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 A meta-analysis of five studies showed a 50% decreased risk of AD in patients with a history of cancer, and a 36% decreased risk of cancer in patients with AD. 12 Two studies using administrative databases have been large enough to examine the relationship between AD and individual cancer types, 4, 5 and significant inverse associations were seen with hematologic malignancies, lung cancer and colorectal cancer.…”
Section: 1 Introductionmentioning
confidence: 99%
“…By contrast, inverse co-morbidities are defined as a lower-than-expected probability of a specific disease in individuals diagnosed with another medical condition. For instance, AD is associated with a lower risk of various cancers, including LC 9, 10 .…”
Section: Introductionmentioning
confidence: 99%